Anomalia de ações de baixo risco: extensão dos estudos no mercado brasileiro - Costa, Alexandre Berlanda (Universidade do Vale do Rio dos Sinos, 2015)
The existence of the Low-Beta Stocks Anomaly (LBSA) conflicts with two traditional economic theories: the efficient-market hypothesis and the risk-return tradeoff. This anomaly could allow market participants to exploit a market inefficiency through adopting a strategy of investing in low risk stocks, hence obtaining superior returns compared to those of higher risk stocks. Previous studies have identified the presence of the AABR in the Brazilian market. This research investigates not only the presence of the LBSA in the Brazilian Market but also its persistence and magnitude of the LBSA by using five asset pricing models, including factors such as market risk, size, value, momentum and illiquidity. The method adopted herein consists in analyzing the performance of stocks’ portfolios (Qn) that were built based on the market beta coefficients obtained in each model. This performance was evaluated through four performance measures. Stock’s portfolios were build with stocks traded in the BM&FBOVESPA stock exchange, in the period 2001-2013. Stocks’ beta coefficients were estimated considering the IBOVESPA index’s theoretical portfolio as a proxy for the market portfolio. Through the comparison of Q1 and Q5 portfolios’ performance, it was possible to identify the presence and persistence of the LSBA in most of the portfolio building and holding strategies adopted. The results, however persistent and economically significant, were not statistically significant. Comparing the different asset pricing models, the Two-Factor model achieved the best results in all performance measures, demonstrating the importance of the liquidity effect on the choice of the assets to exploit the LBSA.
Keywords: Risco e retorno; CAPM; Investimentos; Apreçamento de ativos; Anomalia; Risk and return; Investments; Asset pricing; Anomaly; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis